Invasive dorsal vertebral hemangioma - Rodríguez, Emilio; Martini, Edelweiss; Garavaglia, Federico; Jalil, Raúl; Pueyrredón, Francisco; Muñoz, Adrián (Revista Argentina de Neurocirugía, 2025)
Background: vertebral hemangiomas (VH) are the most common primary bone tumors of the spine and, although rarely symptomatic, can present significant challenges. Currently, there is no consensus on the optimal treatment, with several therapeutic options available both in isolation and in combination, including vertebroplasty, sclerotherapy, surgery, embolization and radiotherapy.Objective: to present a case of invasive vertebral hemangioma with a multimodal treatment approach.Case description: an 11-year-old male patient was admitted for back pain, severe progressive paraparesis and urinary retention. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed a lesion at D8 and D9 levels. Due to the progression of symptoms, surgical treatment was indicated.Surgery: D8 and D9 laminectomy with excision of the epidural component. He presented an extradural hematoma as a complication, for which he was reoperated. The pathology was compatible with vertebral hemangioma. Complementary treatment was performed by means of tumor embolization with n-butyl-2-cyanoacrylate. The follow-up MRI, performed three months after treatment, did not show progression of the disease. Nine months after surgery, the patient is asymptomatic and without neurological deficit.Conclusion: in patients with Enneking III HV associated with a neurological deficit due to compression of the nervous system, surgical treatment is the option of choice. Embolization can be used preoperatively or as a postoperative adjuvant treatment, although its long-term results are still variable, so the patient should be monitored periodically.
Keywords: Embolization; Hemangioma; Radiotherapy; Surgery